ANALYSIS SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION - Andre , Jessica; Alex P, Alex P; Erix, Erix; Citra , Stevannie; Wijaya , Soecipto (International Journal of Social and Management Studies, 2020)
The objectives of this research are as follows: To know the service quality towards customer satisfaction in Front Office department. To know the relationship service quality Front Office department. Quality provides an impetus to customers to establish strong ties with the company. In the long term bond these relationships allow companies to understand carefully the customer's expectations and requirements. Thus, companies can increase customer satisfaction. Quality of service and customer satisfaction closely related company. The higher the level of satisfaction results produce higher customer satisfaction, which helps high prices and a reduction in spending. The purpose of this study was to determine the effect of service quality on customer satisfaction at the Grand Aston City Hall Medan. The author uses the technique sample of 100 people and the research method used is descriptive analysis method, correlation coefficient, determinant coefficient, simple linear regression Results from this study is there the effect of service quality on customer satisfaction at the Grand Aston City Hall Medan. From the correlation test, there is a positive relationship between service quality and customer satisfaction at the Grand Aston City Hall Medan. Variable Y (Customer Satisfaction) is affected by the variable X (Quality of Service) of 29.4% and the remaining 70.6% is influenced by other factors. Linear regression formula is Y = 21.919 + 0,448X. It can be concluded that the higher the variable X (Quality of Service), the higher the variable Y (Satisfaction Customer Satisfaction). If there is no quality of service, the customer satisfaction will be at 21.919. If an increase in the quality of services in one unit, then customer satisfaction will be increased in 0.448. Most respondents agree with the quality of service at the Grand Aston City Hall Medan. In addition, most of the respondents agree with customer satisfaction at the Grand Aston City Hall Medan.